Can Climate Interventions Open Up Space for Transformation? Examining the Case of Climate-Smart Agriculture (CSA) in Uganda - Eriksen, Siri Hallstrom; Cramer, Laura Katherine; Vetrhus, Ingvild; Thornton, Philip (Frontiers in Sustainable Food Systems, 2019)
In this paper, we investigate the ways in which climate change-related interventions such as climate-smart agriculture (CSA) may open up – or close down - spaces for transformation. We explore the interface between worldviews, power relations and policy interventions, focusing in particular on the way that assymetric gender and expert-farmer relations may be reinforced or contested through climate-smart agricultural interventions. It has been argued that fundamental changes required in the face of climate change can only take place through transformation across the personal, practical and political spheres. In particular, it is in the interaction between these spheres where spaces for transformation lie; for example, in the contesting of subjectivities casting farmers as passive recipients of expert advice, in the assumptions regarding what constitutes ‘good , and in how worldviews frame the way we see human-nature relations. Nevertheless, interventions like CSA are often focused mainly on changes to practices or technologies, rather than on how power relations or worldviews shape practices, food security and inequity. Through a case study of Hoima, Uganda, we examine the ways in which the implementation of climate-smart agriculture reinforces existing subjectivities and authority relations or opens up for new (and potentially more emancipatory) subjectivities. First, we describe food security and social inequality drawing on survey data from Hoima. Next, we examine how social actors such as farmers, project workers, local leaders, and government officials position particular farmers or practices as good/progressive or problematic/traditional. We then analyse how these subjectivities reflect authority relations, and the ways in which CSA reinforces or creates space for contesting these. We argue that a focus on commercial agriculture as ‘good’ by many social actors persists also within CSA activities, and is intertwined with asymmetric gender and expert-farmer relations. Commercialisation takes place within the need to increase agricultural production to feed growing urban populations. However, commercialisation for the case of Uganda has also entailed state attempts to govern farmers through farmer associations, the institutional set-up through which CSA often works. A closer attention to these dynamics could potentially help create deeper transformational change through climate-smart agriculture and related climate change interventions.